Anita, the duckling diva Anita, and bibeng biritera - Smith, Anne Curtis (UNICEF, 2015)
"Are you shy? Anita, the duckling diva tells the story of how a little duckling overcomes her shyness with a little help from her family and friends."--Page 4 of cover.